Bottle Creek : a Pensacola culture site in South Alabama - Brown, Ian W.; Drooker, Penelope B. (University of Alabama Press, 2003)
This is the first comprehensive study and analysis of the most important Mississippian mound site on the north-central Gulf coast. Consisting of 18 earthen mounds and numerous additional habitation areas dating to A.D. 1250-1550, the Bottle Creek site was first professionally investigated in 1932 when David L. DeJarnette of the Alabama Museum of Natural History began work there to determine if the site had a cultural relationship with Moundville, connected to the north by a river system. Although partially mapped in the 1880s, Bottle Creek's location in the vast Mobile-Tensaw Delta of Baldwin.